Weighing research competencies of department of English language education graduates at UIN Ar-Raniry Banda Aceh - Dahliana, Syarifah; Akmal, Saiful; Phonna, Rizka Malda (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The purpose of this study is to scrutinize participants’ research competency, source of research competency, and problems related to the research conduct. Nine graduates of the Department of English Language Education were purposefully selected; three of them completed their theses in one semester, three others finished in two semesters, and one other finalized in three semesters. In this qualitative study, semi-structured interviews were used. The findings revealed that graduates with one-semester thesis completion rates have stronger research proficiency than other groups. They have a higher motivational value component, a higher methodology-reflective component, and a higher operational activity component of research competency. Meanwhile, the emotional-volitional component of research competency remains equal for each group of participants. Furthermore, graduates acquired research competency through coursework, research conduct, and self-study. In terms of problems with research conduct, the data disclosed that graduates frequently struggled with self-motivation, supervisors, time/class schedule, knowledge of prior studies, data analysis, and participants selection.